Perancangan Aplikasi Pengamanan File Menggunakan Algoritma Paillier Berbasis Android - Yazirwan Yazirwan (Jurnal Sistem Komputer dan Informatika (JSON), 2021)
Data security and confidentiality issues are one of the important aspects in terms of information exchange. One solution to maintaining the security and confidentiality of files is an encryption technique as an encryption and decryption key. This research describes the development of cryptography (encryption and decryption) that implements the Paillier algorithm. The purpose of Paul's algorithm was chosen because it is a Caesarean algorithm, where Paul's algorithm uses two keys. This research produces an application program that aims to increase file security. In making this application, the method used is Paillier's Algorithm, because it is very suitable for file security that results in completing encryption processes and descriptions. This application is made with the Android programming language and the creation of a file security application with an encryption and description process using the Paillier algorithm, which is expected to solve this problem.